The effect of surfactant concentration on the interlayer structure of organoclay - Nuntiya A. (2014)
An understanding of the interlayer structure of organoclays is of importance in the design of organoclay-based materials and their industrial applications. In this study, X-ray diffraction (XRD), thermogravimetric analysis (TGA) and transmission electron microscopy (TEM) were used to provide new insights into the interlayer structure of organoclays. XRD patterns showed the changes in the d(001) spacings, which gave details of the arrangement of surfactant in the organoclays. The d(001) values of 1.0, 2.0 and 3.0 CEC were 21.85, 35.85 and 36.46 Å Thermal decomposition of organoclays was characterized by TGA. The concentration of 1.0, 2.0 and 3.0 CEC were given weight loss of 20.89, 32.69 and 37.62%, respectively. TEM micrographs showed the interlayer expansion of organoclays which corresponding to the results of XRD. The organoclay which intercalated with HDTMA equivalent to 1.0, 2.0 and 3.0 times of CEC showed interplanar spacings of ∼21, ∼34 and ∼35,Å respectively. Variation in the d-spacing, thermal decomposition and expanded layers of organoclay was found to be a step function of the surfactant concentration.